Removable gingival epithesis: esthetic and quick alternative resolution for anterior periodontal tissue replacement - Cátia Maria Fonseca Guerral; Niara Branco; Sandra Moraes; Adriana da Fonte Porto Carreiro; Bruna Aguiar do Amaral (Faculdade São Leopoldo Mandic, 2008)
The gingiva, part of the masticatory mucosa tissue that covers the alveolar process and surrounds the cervical portion of teeth, has a definitive shape and texture associated with the eruption of teeth. Therefore, it must be included in rehabilitative planning, as the absence of papillae induces problems with esthetics, phonetics and food-impaction. The purpose of the present study was to approach the indications, limitations and techniques for making a removable artificial gingiva made of acrylic resin, by reporting on a clinical case. The patient, a 29-year-old woman, with the sequelae of periodontal disease, presented loss of interdental papilla causing "black holes". She was dissatisfied with the esthetic appearance of her teeth, and also complained of long teeth and air escaping when she spoke. As treatment, prosthetic reconstruction was proposed, by means of a removable artificial gingiva (gingival epithesis) to simulate the presence of interdental papillae, providing better esthetics and phonetics. Gingival epithesis is an easily made, inserted and hygienically cleaned appliance that provides a simple and safe alternative solution for cases in which surgical techniques are limited.